Mediji in spontani nacionalizem - Pušnik, Maruša (Teorija in praksa, 2021)
The article analyses representations of Melania Trump in Slovenian print media and investigates how spontaneous nationalism was constructed in articles about Melania Trump, which in the media was related to promotion of the Slovenian nation by presenting Melania as a brand. The power of national ties, ideas and tradition is maintained and redistributed through the media and popular culture and this leads the authors, unlike the literature in this field that mostly treats the media only as mediators, to also critically address the role played by the media as independent agents in this process of branding the nation. The authors analyse 594 articles about Melania Trump published in Slovenian print media over a period of 3 months in 2016 and 2017. The mentioned analysis showed that the many, recurring media representations of "Melania" have pushed Slovenian nationalism into a commercial context and thereby transformed the nation into a commodity
Keywords: commodification; First Lady; komodifikacija; Mass media; media discourse; medijski diskurz; Melania Trump; Množični mediji; Nacionalizem; nation branding; Nationalism; prva dama; Trump, Melania; znamčenje nacije